Munazara and (non-)Authoritarian Argumentation - Sadek, Karim (Informal Logic, 2025)
I argue for broadening contemporary argumentation theory’s normative scope by introducing a novel category of argumentative norms that synthesize virtue-theoretic and procedural rules. These norms are derived from munazara, a discipline distinguished by its systematic integration of ethics into procedural rules. Framed within normative democratic theory, I advocate the requirement of non-authoritarian argumentation for regulating public debate, targeting how reasons are exchanged, not which reasons are offered. My contention is that munazara’s ethical-procedural norms not only enrich argumentation’s normative toolbox but also enable the operationalization of democratically enhancing public debate.